Understanding the interactive effects of volatile compounds contributing to 'stone fruit' aroma nuances in white wines. (21st December 2021) - Espinase Nandorfy, D.; Siebert, T.; Watson, F.; Keast, R.; Francis, I.L.
Abstract: Background and Aims: The sensory experience of wine aroma is challenging to study. Given the presence of numerous and trace level volatiles, the subtle aroma nuances involved, as well as the complexity of human odour processing, the contribution of individual compounds and mixtures can be difficult to determine. In white wines, the volatile compounds eliciting stone fruit aromas are not well understood. Methods and Results: Factorial designs were used with odorants added to model wine and assessed using sensory quantitative descriptive analysis. In model Viognier‐like wines, several monoterpenes were confirmed to convey stone fruit attributes Apricot and Peach, which were strongly suppressed by aldehydes which imparted Cardboard ‐ like odours. Importantly, lactones increased Apricot aroma when combined with the monoterpenes. For model unoaked Australian Chardonnay wine, sensory‐directed screening followed by factorial studies showed that aliphatic ethyl esters, in particular ethyl octanoate, directed Peach aroma. Fatty acids were strong suppressors of the Peach attribute and gave Cheesy odours. Conclusions: Apricot and peach aromas in Viognier and Chardonnay, although perceptually similar, were caused by different chemical compound families: grape‐derived monoterpenes with lactones and yeast‐derived fatty acid ethyl esters, respectively. Significance of the Study: Having confirmed the compounds responsible for apricot and peach white wine aromas, there is potential to modify their concentration through established viticultural and winemaking practices.